Biofilm infections - Bjarnsholt, Thomas; Jensen, Peter Østrup; Moser, Claus; Høiby, Niels (Springer eBooks., 2011)
There has been an increasing interest and emphasis on the sessile bacterial lifestyle biofilms since it was discovered that the vast majority of the total microbial biomass exists as biofilms. Leeuwenhoek first described the aggregation of bacteria in 1677, but it was only recently recognized as being important in chronic infection. In 1993, the American Society for Microbiology (ASM) recognized that the biofilm mode of growth was relevant to microbiology. This book covers both the evidence for biofilms in many chronic bacterial infections as well as the problems facing these infections such as diagnostics, pathogenesis, treatment regimes, and in vitro and in vivo models for studying biofilms. This is the first scientific book on biofilm infections, with chapters written by world- renowned scientists and clinicians. The intended audience of this book includes scientists, teachers at the university level, as well as clinicians. About the Editors: Thomas Bjarnsholt, Ph.D., Technical University of Denmark, Lyngby, Denmark Peter Oestrup Jensen, Dept. of Clinical Microbiology, Rigshospitalet, Copenhagen, Denmark Claus Moser, Ph.D., Dept. of Clinical Microbiology, Rigshospitalet, Copenhagen, Denmark Niels Hoeby, Dept. of Clinical Microbiology, Rigshospitalet, Copenhagen, Denmark